CONSUMER MOTIVATIONS, ATTITUDE AND BEHAVIORAL INTENTION TOWARD GREEN HOTEL SELECTION - Lei Wang; Zi-Xu Wang; Philip Pong Weng Wong; Qi Zhang (School of Tourism, Universitas Ciputra Surabaya, 2021)
Most prior studies have investigated the relationship between green purchase attitude and behaviorbased on the Theory of Planned Behavior (TPB). However, TPB is a behavioral theory based on acausal process, and thus ignores consumers’ motivational aspects. The purpose of this study is toexamine consumers’ motivational variables, in which monetary, convenience (location), hedonic andvirtual motivation (social media) influence consumers’ intentions to visit green hotels based ongenerational characteristics. A survey questionnaire was developed where a total of 775 questionnaireswere ultimately collected followed by subsequent empirical testing of the postulated hypotheses usingSPSS and Structural Equation Modelling. The results suggest monetary and virtual motivation positivelyinfluence green purchase attitude (GPA) respectively, while convenience negatively influence GPA.GPA displays a positive influence on green purchase intention (GPI) while hedonic motivation plays norole in this study. In addition, statistically significant differences in monetary, convenience, hedonic,virtual motivation and GPI were observed between generations of consumers towards green hotelselection. The theoretical and practical implications of the results were highlighted, including limitationsof the research. Lastly, this study addressed the relationship between motivational traits and behavioralintention in the hospitality and tourism field, and its results will provide useful information for greenhotels’ stakeholders.